A secure multi‐path transmission algorithm based on fountain codes. Issue 5 (29th January 2022) - Liu, Jianhang; Xu, Jingshuai; Li, Shibao; Cui, Xuerong; Zhang, Yucheng
Abstract: Cyber security is the basis of ensuring reliable network transmission. In addition to encrypting the data, dividing the data into multiple paths for transmission is also an important way to improve the security. However, the development of semantic analysis algorithms leads to the fact that the eavesdroppers can restore the data as long as they obtain the data on the part of the paths, which reduces the security of multi‐path transmission. Additionally, in the environment of poor communication quality, retransmission mechanism leads to long transmission delay. To solve the above problems, this article proposes a secure multi‐path transmission algorithm based on fountain codes—FMPST. According to the safety level of data, the forwarding nodes are dynamically selected. Making use of the non‐feedback characteristic of fountain codes can not only reduce data delay, but also evaluate the channel packet loss rate by random forest model. FMPST can calculate the number of packets by packet loss rate, which makes it difficult for eavesdroppers to obtain enough packets to decrypt. The experiments show that compared with other multi‐path transmission algorithms, FMPST can improve the data security more than three times and reduce the communication delay by at least 50%. Abstract : FMPST selects the forwarding nodes according to the data security level, which cancels the restriction of path disjoint, and uses the fountain codes to predict the packet loss rate according to the improved random forest to achieve no feedback transmission.